A major plant practice in General Tuna Corporation, Brgy. Tambler, General Santos City - Relox, Paquito Jr. Enclonar (2007)
The student was immersed for a total of no less than 288 hours in the actual plant operations processing canned and pouch tuna in General Tuna Corporation at Tambler, General Santos City. The student was exposed to the work of a quality control officer and was assigned in the receiving, precooking, loining, packing, seeming, retort, and case-up in-line processing sections. The exposure provided the student with actual experience in applying the HACCP principles learned from classroom. He was able to participate in the implementation of the HACCP program designed for packing tuna in cans and pouches, which involves the preventive and corrective measures for quality and hazard control. A fraction of the plant practice period was also spent in the Quality Assurance Department, which exposed him to sensory, microbiological, and physic-chemical inspection for raw materials (e.g. empty cans, pouches, and fish) and finished products. His stay in the company also made him aware of the value of developing good working relationships with co-workers. Aided by his academic training, he was able to rationalize the processes being done in the company in the light of science and technology derived from classroom instructions